Resistance To Change Among First Line Managers In Multinational Organizations In Malaysia - M. S. Wafi, Shaban (2008)

(untitled)
Dramatic changes in organization structure and culture have become an essence that more and more individuals and organizations are recognizing the importance of the way that they can overcome the resistance to change.